Proceedings of the Fourth Annual IEEE International Workshop on Workload Characterization. WWC-4 (Cat. No.01EX538)
DOI: 10.1109/wwc.2001.990753
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model of the supercomputer workload

Abstract: As with any computer system, the performance of supercomputers depends upon the workloah that serve as their input. Unfortunately, however, there are many important aspects of the supercomputer workloads that have not been modeled, or that have being modeled only incipiently. This paper attacks this problem by considering requested time (and its relation with execution time) and the possibility of j o b cancellation, two aspects of the supercomputer workload that have not been modeled yet. Moreover, we also im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
2

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 19 publications
2
113
0
2
Order By: Relevance
“…An interesting compromise is to keep such data and explicitly include it in the workload model [137]. In other words, part of the workload model will be to model how often jobs fail or are aborted by the user who submitted them, or how often requests are made to download non-existent files.…”
Section: Noise and Errorsmentioning
confidence: 99%
See 3 more Smart Citations
“…An interesting compromise is to keep such data and explicitly include it in the workload model [137]. In other words, part of the workload model will be to model how often jobs fail or are aborted by the user who submitted them, or how often requests are made to download non-existent files.…”
Section: Noise and Errorsmentioning
confidence: 99%
“…A more general procedure that was advocated by Cirne and Berman is to use clustering as a means to distinguish between "normal" and "abnormal" data [137]. The methodology is to partition the workload log into days, and then to characterize each day by a vector of length n (specifically, this was applied to the modeling of the daily arrival cycle, and the vector contained the coefficients of a polynomial describing it).…”
Section: Identifying Noise and Anomaliesmentioning
confidence: 99%
See 2 more Smart Citations
“…In such scenarios, users have to provision the worst-case capacity as the upper bound. Third, users tend to overestimate their resource needs for the sake of safe execution, as illustrated by a supercomputing workload study that concluded that half of all jobs used less than 20% of the requested capacity [3].…”
Section: Introductionmentioning
confidence: 99%